Perancangan Audio Tour Guide Desa Wisata Keris Aeng Tong Tong Sumenep Berbasis QR Code - Hujairi, Ahmad Walid; Khoironi; Fardiansyah Putra, Deny; Aguestien, Lusiana; Prasetyo, Joko (Politeknik Negeri Jember, 2024)
Since the recognition of keris as an intangible heritage by UNESCO in 2005, and the determination of Sumenep Regency as a keris city, the development of keris in this region has continued to increase. Aeng Tong-Tong Village, which has the largest number of masters in the world, has become a national and international spotlight. However, supporting tourism infrastructure is still limited, such as a lack of directions, minimal information about masters and keris, and limited English language skills of local guides. This community service activity focuses on designing the Audio Tour Guide application, a mobile-based tour guide system that makes it easier for tourists to explore the village through QR code and multi-language features. This application provides biographical information about masters and descriptions of keris collections in audio in two languages, Indonesian and English. The application development stages use the multimedia development life cycle (MDLC), including concept, design, data collection, assembly, and testing. The results of the application trial to 32 respondents showed that the application was considered very good in terms of ease of use, graphic quality, audio quality, and ability to provide information, although there is still room for improvement in terms of graphics and audio.